Effectiveness of Lavender Aromatherapy for Sleep Disorders in Older Adults: A Systematic Review - Mohammad Alfian Faisol Mustaqim; Setyo Adi Nugroho; S. Tauriana (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2026)
Sleep disorders among older adults are a growing global health concern that negatively affect physical health, psychological well-being, and quality of life. Non-pharmacological interventions are increasingly recommended due to the risks associated with long-term use of sleep medications in elderly populations. Lavender aromatherapy has emerged as a complementary therapy with potential benefits for improving sleep quality and reducing insomnia. This study aims to identify and analyze the effectiveness of lavender aromatherapy as a complementary intervention for managing sleep disorders in older adults. A systematic review design was employed using the PRISMA framework to identify relevant studies published between 2020 and 2025. Literature searches were conducted through Google Scholar, ScienceDirect, and Portal Garuda databases using predefined keywords and inclusion criteria based on the PICOS framework. Seven eligible studies were included and analyzed narratively to evaluate intervention methods, duration, and outcomes related to sleep quality and insomnia severity. The findings indicate that lavender aromatherapy, either as a single intervention or combined with therapies such as music, acupressure, or massage, consistently improves sleep quality and reduces insomnia symptoms among older adults. The therapy is safe, cost-effective, and easily implemented in community and clinical settings. Overall, lavender aromatherapy is a promising complementary intervention that can be integrated into holistic geriatric and nursing care to support healthy aging and improve quality of life. Keywords: aromatherapy; complementary therapy; elderly; insomnia; lavender; sleep quality.